On the Relationship Between White Matter Structure and Subjective Pain. Lessons From an Acute Surgical Pain Model - Torrecillas-Martínez, Laura; Catena, Andrés; O'Valle, Francisco; Solano-Galvis, César; Padial-Molina, Miguel; Galindo-Moreno, Pablo (Frontiers in Human Neuroscience, 2020)
Background: Pain has been associated to structural changes of the brain. However, evidence regarding white matter changes in response to acute pain protocols is still scarce. In the present study, we assess the existence of differences in brain white matter related to pain intensity reported by patients undergoing surgical removal of a mandibular impacted third molar using diffusion tensor imaging (DTI) analysis. Methods: 30 participants were included. Subjective pain was reported using a visual analogue scale at three post-surgical stages: under anesthesia, in pain, and after the administration of an analgesic. The diffusion data were acquired prior to surgery. Results: DTI analysis yielded significant positive associations of fractional anisotropy in white matter areas related to pain processing (corticospinal tract, corona radiata, corpus callosum) with the differences in pain between the three post-surgery stages. Extent and location of these associations depended on the magnitude of the subjective pain differences. Tractography analysis indicated that some pain-tract associations are significant only when pain stage is involved in the contrast (posterior corona radiata), while others (middle cerebelar peduncle, pontine crossing) are only when anesthesia is involved in the contrast. Conclusions: The association of white matter fractional anisotropy and connectivity, measured before the pain stages, with subjective pain depends on the magnitude of the differences in pain scores.